URGENSI BELAJAR TAHSIN BAGI SISWA SEKOLAH DASAR DALAM MENINGKATKAN KUALITAS BACAAN AL-QUR'AN - Alda Eky Nur Kholifah; Auliyah Nazal Qur’ani (Al-Kindi, 2025)
Tahsin learning holds significant urgency in improving the quality of Qur’anic recitation, especially for elementary school students who are at the early stage of character development and religious understanding. Tahsin refers to the process of correcting and perfecting Qur’anic recitation in accordance with the rules of tajwid, makharijul huruf (articulation points), and the etiquette of recitation. This study aims to highlight the importance of tahsin education for elementary students in order to build a strong foundation for accurate and meaningful Qur’anic reading. The research employs a descriptive qualitative approach with data collected through observation, interviews, and literature review. The findings indicate that tahsin learning at the elementary level not only helps students recite the Qur’an fluently and in accordance with tajwid, but also boosts self-confidence, nurtures a love for the Qur’an, and strengthens spiritual values in daily life. Moreover, the presence of competent teachers in tahsin plays a crucial role in the success of this learning process. Therefore, the urgency of tahsin education should not be overlooked in Islamic educational systems at the elementary level, considering its significant impact on the holistic religious development of students.